Regiodivergent C−H and Decarboxylative C−C Alkylation by Ruthenium Catalysis: ortho versus meta Position‐Selectivity. Issue 42 (25th August 2020) - Korvorapun, Korkit; Moselage, Marc; Struwe, Julia; Rogge, Torben; Messinis, Antonis M.; Ackermann, Lutz
Abstract: Ruthenium(II)biscarboxylate complexes enabled the selective alkylation of C−H and C−C bonds at the ortho ‐ or meta ‐position. ortho ‐C−H Alkylations were achieved with 4‐, 5‐ as well as 6‐membered halocycloalkanes. Furthermore, the judicious choice of the directing group allowed for a full control of ortho‐/meta ‐selectivities. Detailed mechanistic studies by experiment and computation were performed and provided strong support for an oxidative addition/reductive elimination process for ortho ‐alkylations, while a homolytic C−X cleavage was operative for the meta ‐selective transformations. Abstract : Ortho vs. meta : C−H alkylations of arylpyrazoles are achieved through ruthenium‐catalyzed C−H or C−C activation. The site‐selectivity is controlled by the pyrazole substituents and the steric hindrance of the alkyl moiety.